Clonal analysis and dynamic imaging identify multipotency of individual Gallus gallus caudal hindbrain neural crest cells toward cardiac and enteric fates - Weiyi Tang (Nature Portfolio, 2021)
Neural crest stem cells formed from the caudal hindbrain migrate long distances to the heart and gut, but how cell fate is determined is unclear. Here, the authors use multiplex clonal analysis and single-cell photoconversion lineage tracing to show environmental not intrinsic factors affect the cell fate of multipotent caudal hindbrain cells in the chick.